E-library relevance and adequacy as predictors of e-library usage among undergraduate students in Tai Solarin University of Education, Ogun State, Nigeria (2013)
Evaluating e-library services is usually based on users'feedback, precision rate, the proportion of the retrieved documents that are relevant to the query. This is precisely what this paper is focused on. The data for this study were collected with the use of questionnaire. The copies of the questionnaire were administered to solicit the response of the undergraduate students on their satisfaction with TASUED e-library and how adequate and relevant the undergraduate students found the e-library resources at TASUED. It was discovered that the undergraduate students are satisfied with the overall performance of the electronic library, most especially in terms of value of service, access to information, response time, ease of use and quantity of collections.